Safety evaluation of α-galacto-oligosaccharides for use in infant formulas investigated in neonatal piglets. (26th July 2017) - Kruger, Claire; Zhou, Yuting; Thorsrud, Bjorn A; Morel-Despeisse, Fanny; Chappuis, Eric
Galacto-oligosaccharide (GOS), comprising galactoses with a glucose or sucrose, is a family of nondigestible oligosaccharides. The present study evaluates the safety of an α-GOS product (P-GOS ® P) in a neonatal piglet model for 3 weeks. Three days after birth, neonatal piglets were divided into control and treated groups and provided with swine milk replacers in the absence and presence of 8 mg/mL—of the α-GOS product, respectively. An increase in the weight of the large intestines in treated males was noted, which is a common finding in studies of animals fed nondigestible oligosaccharides. There were no α-GOS product-related adverse effects in the piglets in terms of clinical signs, body weights, feed consumption, clinical chemistry, hematology, organ weights, or histopathology. The study demonstrated that formula supplemented with 8 mg/mL of P-GOS P is safe and well tolerated in neonatal piglets and supports the safe use of P-GOS P in infant formulas.